DETERMINANTES DEL DESEMPLEO JUVENIL EN ECUADOR: UN ENFOQUE REGIONAL USANDO MODELOS LOGIT MULTINIVEL, PERIODO 2012-2016 - Vicente Guayanay, Irene Fabiola (2018)
Unemployment is a problem that has been going on for many years, so the main objective of all government is to reduce it. Among the most affected by this phenomenon are mainly young people because of their working conditions. It is considered that the high rate of youth unemployment is the result of the lack of education that is usually accompanied by the lack of work experience, additional to that, the labour market plays an important role in the process of labor insertion. In this scenario arose the present topic of investigation, whose general objective is, to establish the determinants of the regional youth unemployment in Ecuador, through a descriptive-econometric study, period 2012-2016. The necessary information was taken from the following databases: national survey on employment, unemployment and underemployment (ENEMDU); Business directory (DIE); National Information System (SNI); And, national Secretariat of Higher Education, science, Technology and Innovation (SENESCYT) of the period 2012-2016. The scientific method was used with its modalities: inductive, deductive, analytical, synthetic and statistical. Likewise, the techniques applied were the bibliography and the statistic with their respective instruments that are: The bibliographic file, Microsoft Excel and Stata. The results show that both the individual characteristics (age, gender, level of education and experience) and the regional characteristics (public investment and number of companies) have a significant influence on youth unemployment, thus improving Conditions in both respects would help to reduce unemployment.